Apoptosis-induced chromosome breaks and chromosome rearrangements at mixed lineage leukaemia breakpoint cluster region in nasopharyngeal and leukaemia cells - Siaw, Grace Ee Lu (Universiti Malaysia Sarawak (UNIMAS), 2008)
Chromosome rearrangements such as additions, deletions, translocations and inversions are commonly observed in various types of cancer. In leukaemia, the Mixed Lineage Leukaemia (MLL) gene on chromosome llq23 had been found to translocate with many partner genes, resulting in the generation of fusion genes. Chromosomal deletions and additions at llq23 had been reported in nasopharyngeal carcinoma (NPC) though it was unknown which gene was involved. The apoptotic nuclease was proposed to be involved in these chromosomal rearrangements by fragmenting the genomic DNA into small fragments forming the nucleosomal DNA ladder. In leukaemia, it was possible that the MLL gene and its partner genes were being cleaved during apoptosis. In an effort to rescue the cells, the DNA repair system may erroneously join the DNA fragments, resulting in chromosome translocation. Epstein-Barr virus (EBV) infection and/or other factors may induce apoptosis in NPC cells, resulting in chromosomal breaks and subsequent rejoining may take place during the attempted DNA repair. As a result, the surviving cells may harbour chromosome rearrangements such as deletions. Therefore, the aim of this study was to detect apoptosis-induced chromosome breaks and rearrangements using NPC and leukaemic cell lines as model systems. These cell lines were induced to undergo apoptosis by overgrowing the cells to high densities followed by revival in fresh medium to rescue them. The leukaemic cells were also induced to undergo apoptosis by treatment for short time period with the low and high concentrations of etoposide (VP-16). This was followed by revival of the apoptotic cells in fresh medium to rescue them. In addition, both the NPC and leukaemic cells were also treated with different concentrations of hydrogen peroxide (H202) to induce apoptosis. Subsequently, detection of chromosome rearrangements and breaks was performed. Nested PCR using primers specific for MLL and AF9 (one of the common translocation partners of MLL) was also performed. For NPC cells, nested PCR using the primers specific for the MLL bcr and the telomere were carried out to detect deleted chromosome with telomere sequence added. Our result showed that both the cell density-induced apoptosis in NPC and leukaemic cells generated chromosomal breaks near the 3' end of the MLL bcr. There was no telomere capturelhealing detected at the cleavage sites of the revived NPC cells. The sequenced PCR bands of multiple sizes were found to originate from other chromosomes. Both the 3' and 5' breaks of the MLL bcr were detected in the revived VP-16-treated leukaemic cells. In some of the samples, these 5' breaks were located centromeric to the MLL bcr region. However, no translocation of other genes to the break sites was detected. NPC cells treated with H202 showed chromosomal breaks near the 3' end of the MLL bcr with no telomere sequences added. However, in leukaemic cells, translocation of the MLL bcr with unknown genes from other chromosomes was detected.